The Effect of Digital Literacy and Self-Regulation Ability on The Performance of Junior High School Teachers in Babelan District - Aini, Nurul; Baharuddin; Hermanto (Proceeding International Conference on Education, 2023)
This study aims to determine the effect of digital literacy skills and self-regulation partially or jointly on the performance of junior high school teachers in the Bembelam District. This study uses a quantitative approach using correlational. Data analysis using the Chi Quare Test. The results of the study show that digital literacy skills have a significant effect on teacher performance. Digital Literacy Ability has an influence on Teacher Performance of 60.5%, the R value is 0.752. Self-Regulation has a significant effect on Teacher Performance. And found the value of R square (R) is 0.630. This shows that the self-regulation variable has an influence on teacher performance of 63.0%, and the R value in the table above is 0.774. Digital Literacy ability has a direct positive effect on Self-Regulation which can be accepted. Due to digital literacy skills and good self-regulation will improve quality and affect teacher performance.